Immobilisation of apatite on Ti30Ta alloy surface by electrospinning of PCL - Souza, Marisa Aparecida [UNESP]; Aquiles Carobolante, Joao Pedro [UNESP]; Almeida, Rosemeire dos Santos; d'Avila, Marcos Akira; Walker, Rachael Simon; Popat, Ketul C.; Rosifini Alves Claro, Ana Paula [UNESP] (Ice Publishing, 2017)
Surface modifications of titanium alloy have been extensively researched for the purpose of increasing the biocompatibility of medical implants. In this study, a Ti30Ta alloy surface was modified by functionalisation with electrospun poly(epsilon-caprolactone) (PCL) followed by the immobilisation of apatite (AP) to achieve a bioactive surface. Human adipose-derived stem cells were then cultured on the surfaces for up to 7 d to ensure the effects of PCL and AP treatments on cytocompatibility and cellular fate processes. PCL fibres and alloy surfaces were evaluated with scanning electron microscopy, X-ray diffraction and thermal analysis techniques. The analyses showed a uniform deposition of the electrospun PCL fibres on the entire Ti30Ta alloy surface. In addition, increases in cell growth and proliferation were seen after 7 d. Results indicated that the surface treatment of the Ti30Ta alloy with electrospun fibres and AP immobilisation may increase the bioactivity of the surface and provide a beneficial surface modification for use in biomedical applications.
Keywords: alloys; poly(epsilon-caprolactone); surface modification